2008
DOI: 10.1016/j.mri.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow estimation from perfusion-weighted MRI using FT-based MMSE filtering method

Abstract: Introduction-Perfusion weighted MRI can be used for estimating blood flow parameters using bolus tracking technique based on DSC MRI. In order to extract flow parameters, several deconvolution techniques have been proposed, of which, the SVD and FT based techniques are more popular and widely used. In this work, an FT based method has been proposed that involves derivation of an optimal shaped filter (defined as a filter function) estimated using minimum mean-squared error (MMSE) technique in the frequency dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…FT-based MMSE method is inherently adaptive to the noise level [2] and is more regulatory in low-flow, low-contrast, low-SNR regions so that it potentially does not overestimate the low flow values. The IQR for the NWM were comparable between the techniques.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FT-based MMSE method is inherently adaptive to the noise level [2] and is more regulatory in low-flow, low-contrast, low-SNR regions so that it potentially does not overestimate the low flow values. The IQR for the NWM were comparable between the techniques.…”
Section: Discussionmentioning
confidence: 99%
“…oSVD method uses a fixed oscillation index based on certain SNR assumption, to reject singular values that will be not be used for estimating CBF [5]. On the other hand, the FT-based MMSE method involves estimation of an optimal shaped filter,ϕ*( f ), derived using the minimum mean-squared error method (please see previous publication for derivation of the shaped filter)[2]. The deconvolution methods are essentially mathematical methods used for solving for impulse-residue function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sakoglu et al [110] proposed a FT method including the development of a filter using the minimum mean-squared error in the frequency domain. They found that the technique was stable at low noise levels, but that it underestimated the CBF under moderate noise conditions.…”
Section: Model-independent Deconvolutionmentioning
confidence: 99%